Pengaruh Dimensi Social Media Marketing terhadap Brand Image : Studi Pada Pengguna Brand Rucas - Nayla Kheista Salsabila; Santi Widyaningrum; Teofilus Karnalim; Pieter Sahertian; I Gusti Ngurah Agung Arya Bhakta Narayana (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Social media marketing has become a strategic instrument for local fashion brands to create digital experiences and shape consumer perceptions. This study aims to analyze the effect of social media marketing dimensions consisting of entertainment, interaction, trendiness, and electronic word of mouth (e-WOM) on the brand image of Rucas users. The research employed a quantitative explanatory approach. Data were collected through an online questionnaire using a five-point Likert scale and analyzed using SPSS. The respondents were 146 social media users who knew, viewed, or interacted with Rucas content. Instrument testing showed that all questionnaire items were valid, with item-total correlations above the r-table value and significance values below 0.05. The reliability test also showed strong internal consistency, with Cronbach’s Alpha values ranging from 0.887 to 0.936. The regression results indicate that interaction, trendiness, and e-WOM have a positive and significant effect on brand image, while entertainment has a positive but insignificant effect. Simultaneously, all four dimensions significantly influence brand image, with e-WOM as the strongest predictor. These findings imply that local fashion brands need to strengthen two-way communication, trend-based content, and positive consumer conversations to build a stronger brand image in digital platforms.